2020
DOI: 10.22369/issn.2153-4136/11/1/15
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effectiveness of an Online Learning Platform in Transitioning Users from a High Performance Computing to a Commercial Cloud Computing Environment

Abstract: Developments in large scale computing environments have led to design of workflows that rely on containers and analytics platform that are well supported by the commercial cloud. The National Science Foundation also envisions a future in science and engineering that includes commercial cloud service providers (CSPs) such as Amazon Web Services, Azure and Google Cloud. These twin forces have made researchers consider the commercial cloud as an alternative option to current high performance computing (HPC) envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The last couple of semesters have shown us the strengths of adopting an online-only approach. As a nation, we have collectively observed that training over online resources has its own share of questions related to access, inclusivity, equity, and diversity [6]. While we celebrate the expanded reach enabled by offering training over the Internet, we sadly realize that students with limited access to technology and reliable Internet connectivity are in danger of being left behind.…”
Section: Challenges and Future Workmentioning
confidence: 98%
See 2 more Smart Citations
“…The last couple of semesters have shown us the strengths of adopting an online-only approach. As a nation, we have collectively observed that training over online resources has its own share of questions related to access, inclusivity, equity, and diversity [6]. While we celebrate the expanded reach enabled by offering training over the Internet, we sadly realize that students with limited access to technology and reliable Internet connectivity are in danger of being left behind.…”
Section: Challenges and Future Workmentioning
confidence: 98%
“…Much like other campus research computing efforts, Texas A&M HPRC has offered a series of training, outreach, and educational efforts that supports our researcher community [2][3][4][5][6]. Our user training program has been operational for several years, with thousands of participants signing up for events.…”
Section: Online Training and Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, "quality of life" features that are common in AI/ML toolkits on public cloud-based environments are often not available on these resources. We have previously reported on our work in advancing the state of CI-training at Texas A&M. Texas A&M High Performance Research Computing (HPRC) offers over sixty training seminars, courses, workshops, and week-long computing-camps that support CI aspirations ranging from middle school students to CI professionals [3][4][5][6][7][8][9][10]. During the COVID-19 pandemic-imposed workplace changes, we have learned that pedagogical approaches commonly adopted in in-person environments do not translate to a virtual learning setting.…”
Section: Introductionmentioning
confidence: 99%
“…Texas A&M High Performance Research Computing has abundant experience developing informal courses and pedagogical approaches tailored for specific user groups [3][4][5][6][7][8][9][10]. These courses cover a wide scope of topics including introductions to our HPC systems and Linux basics; programming in Python, R, Matlab, and Pearl; and bioinformatics.…”
Section: Introductionmentioning
confidence: 99%